SORTATION AND GRADING OF CORN HUSK AS RAW MATERIAL FOR FLORAL CREATION HANDICRAFT PRODUCT AT UKM GARUDA JAYA - Elvina Dhiaul Iftitah (Journal of Innovation and Applied Technology, 2017)
Corn husk as the main raw material in making floral creations need to set its quality. UKM Garuda Jaya as a producer of floral creation handicraft from corn husk always try to get the best raw material of corn husk, so that the floral creation handicraft product is also give the beautiful one. UKM Rajawali as a supplier of corn husk, has partnered with UKM Garuda Jaya in providing quality corn husk as raw material. One of the activities in the providing the best of corn husk quality is sorting and grading activities. The goal of these activities are : to gain better and uniform quality, to provide standardization and improvement of the way of processing, and to offer some of quality to the consumer with the appropriate price. The result of two activities are manual prosedure standart for preparation and colouring of corn husk.